Changing rules and configurations during soccer small-sided and conditioned games. How does it impact teams` tactical behavior? - Machado, J. C.; Ribeiro, J.; Ewerton Palheta, C.; Alcantara, C.; Barreira. D.; Guilherme, J.; Garganta, J.; Scaglia, A. J. (Frontiers in Psychology, 2019)
The present study aimed to investigate how team`s tactical behavior varies within and between age categories in different Small-Sided and Conditioned Games` configurations and conditions. Twenty non-elite youth male soccer players (U15, n = 10, mean age = 13.5 ± 1.2 years; U17, n = 10, mean age = 16.3 ± 0.5 years) were selected. Thirty-six Small-Sided and Conditioned Games (SSCG) were played in both categories, namely three Representative SSCG (R-SSCG), three Maintaining Ball Possession Games (MBPG) and three Progression to Target Games (PTG) performed for each configuration (Gk+3vs3+Gk and Gk+4vs4+Gk). Teams` tactical behavior was analyzed based on simple and composite performance indicators, as well as through Lag Sequential Analysis. Rules manipulation and SSCG configurations influenced teams` tactical behavior on both categories, but in different ways. Teams composed by younger players presented greater difficulties in MBPG played in smaller games configuration, while Gk+4vs4+Gk configuration can be used to enhance teams` tactical performance of younger players in R-SSCG and MBPG conditions. Moreover, increasing rules manipulations appeared to negatively impact on teams` exploratory behavior. Therefore, practitioners should carefully manipulate key constraints to adapt task demands to players` age category and training session`s goals in order to enhance tactical performance.